Pengukuran Kecernaan Lemak Kasar, Bahan Organik dan Energi pada Pakan Ikan Nila (Oreochromis niloticus) dengan Menggunakan Teknik Pembedahan [Measurements Of Extract Ether Digestibility, Organic Matter and Energy Feed In Tilapia (Oreochromis niloticus) Using Surgery Techniques] - Agustono Agustono; Rahardian Wicaksono; Widya Paramita Lokapirnasari (Jurnal Ilmiah Perikanan dan Kelautan, 2013)
Abstract Tilapia is a freshwater fish species are widely cultivated in Indonesia. Tilapia production continues to grow every year, the average increase in the number of experienced production tilapia reaches 22.24% in the 2010-2011 range. Tilapia production in 2011 reached 567.449 tons and was second aquaculture production by major commodity after seaweed. This study aimed to determining differences in extract ether digestibility, organic matter, and energy on feed derived from different factories in tilapia (Oreochromis niloticus) using surgery techniques. The research design is using completely randomized design. The variables were measured extract ether digestibility, organic matter, and energy in tilapia feed. Analysis of the data processed using Analysis of Variance (ANOVA) to determine differences in treatment given. If there is a difference then followed by Duncan's Multiple Range Test with a significance level of 5%. Based on the findings that there were no significant differences (p>0.05) in extract ether , organic matter, and energy digestibility of the feed value of tilapia. The results stated that the feed treatments A, B and C efficiently digested by tilapia.